An Assessment of physical-chemical and biological properties of industrial wastewater in Al-Kut textile factory - Hamzah Al-Hachami; Hatam A. Gzar (Wasit Journal of Engineering Sciences)
Most developing countries that bypass rivers are concerned about water pollutants. Water quality within the permissible limits for agricultural, industrial, and drinking reasons is a difficult problem to solve. On the basis of their importance, ten physical and chemical parameters were chosen for this investigation from Al Kut textile factory. For the last eight years, physical-chemical parameters measurements of water samples have been researched for ten parameters are total dissolved solids TDS, TSS, Tur., Electrical conductivity, sulfate SO4, Chloride, Phosphate, COD, DO and biological oxygen demand BOD5. The findings of the water quality examination were compared to the World Health Organization's maximum permitted limit concentration and Iraqi limitations spastically. Moreover, the water quality parameters were gradually decreased according to the findings. Results shows the annual variation of Al-Kut TSS concentration with decreasing rate of (71%), Turbidity concentration with decreasing rate of (11.44%), Chloride and Phosphate concentrations within its decreasing rate of 50 % and 70.23 % respectively during the study period of the last eight years. While the average BOD5 values decrease in concentration and the annual variation of Al-Kut DO concentration within its decreasing rate of (51%) during the study period of the last eight years.